The Analyze of Translation Techniques in Despicable Me 3 Movie (International Journal of Scientific Research and Management (IJSRM), 2024)
Translation is frequently employed to facilitate concept expression in the target language, accelerate language acquisition, and give us more confidence when comprehending words and expressions from other languages. Translation is not merely about converting words from one language to another; it is a comprehensive process that facilitates the expression of concepts in the target language, accelerates language learning, and boosts confidence in understanding foreign words and expressions.For this study, the researcher used a descriptive qualitative research approach. In this research the researcher will translate a movie with the title is ‘Despicable me 3’ to analyze the 18 translation techniques used in the movie. the researcher analyze there are only 14 translation techniques that used in ‘Despicable me 3’ movie.